Account of a recent discovery of Stone Cists, containing Urns and human bones, in the farm of Windymains, Humbie, Haddingtonshire (Proceedings of the Society of Antiquaries of Scotland, 1862)
A local tenant of Windymains in East Lothian, Robert Forman, describes two tombs uncovered during ploughing in the area. He also notes that there have been many other grave sites found locally and that there was once a fortification of some kind nearby.